Analysis of the fermentative profile of yeasts isolated from natural sources (Research, Society and Development, 2021)
The natural environment aggregates an immense amount of microorganisms, some unknown and others still unexplored and that may have the potential for the production of compounds. Thus, this study aims to evaluate the fermentative profile of isolates from natural sources under different growing conditions. For this purpose, the plating performing on a 2% YPD solid medium incubating in an oven at 30 °C. The isolated colonies use for the carbon source assimilation test, which carried out through cell growth. Carrying out in test tubes containing the YP fermentative added with carbon sources (glucose, lactose, sucrose, fructose, mannose, maltose, starch) with a concentration of 17 ºBrix, at pH 4 and 6, incubated at 28 and 35 ºC and at different times of cultivation, aliquots removed for analysis. For the control, the yeast Catanduva-1 was used. The isolates grew in the range of pH 4 and pH 6 at 28 ºC and isolate A4 showed greater growth at a temperature of 35 °C. Isolates A4, A5, and A6 used most sugars except for lactose. Isolate A2 assimilated glucose and fructose and A6 showed a fermentation profile similar to standard yeast.